2019
DOI: 10.1111/1365-2656.13100
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of inverse density‐dependent territorial behaviour and aggression in a monogamous mammal

Abstract: Territoriality is an important process shaping population dynamics, and the defence of a territory is crucial for individuals to increase the duration of territory occupancy and, consequently, reproductive success. However, little is known about how the frequency of territory intrusions and subsequent territorial behaviours and aggression by territory owners are affected by external factors, such as population density. This is important because it can affect mate change (the replacement of one pair member) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 88 publications
0
30
0
Order By: Relevance
“…Territoriality between beaver colonies may therefore function as a mechanism of site‐dependent regulation (Rodenhouse et al 1997), causing average fecundity rates to decrease as population density increases (as previously found by Payne 1984, Pietrek et al 2017). However, a recent study suggests levels of conspecific aggression may actually be inversely density‐dependent as a result of delayed dispersal at high densities (Mayer et al 2020), which may result in lower rates of change at higher densities.…”
Section: Discussionmentioning
confidence: 99%
“…Territoriality between beaver colonies may therefore function as a mechanism of site‐dependent regulation (Rodenhouse et al 1997), causing average fecundity rates to decrease as population density increases (as previously found by Payne 1984, Pietrek et al 2017). However, a recent study suggests levels of conspecific aggression may actually be inversely density‐dependent as a result of delayed dispersal at high densities (Mayer et al 2020), which may result in lower rates of change at higher densities.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 4). Because dispersing beavers are primarily solitary individuals (45), the only way for a newly created or recolonized pond to persist once a wolf kills a dispersing individual is if another dispersing beaver reaches that pond and continues to maintain the dam. Our work suggests that such a scenario is rare and that once a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We counted the family group size for every territory in our study area using a combination of live captures and observations, allowing us to calculate the local population density (hereafter population density) separately for each river and each year (Figure 3), defined as the number of individuals per km shoreline (calculated for both sides of the river) (Mayer et al, 2020).We recorded tail scars every time we (re)captured an individual.…”
Section: Eurasian Beaversmentioning
confidence: 99%
“…Population density can also affect aggression in beavers. Mayer et al (2020) demonstrated that territory owners have more tail scars at lower population densities due to increased intruder pressure via dispersers, because dispersers are more likely to emigrate at lower population densities and remain in their natal family group at high densities when the chances of obtaining a territory are low (Mayer, et al, 2017;Mayer Zedrosser et al, 2017c). Moreover, landscape structure can influence intraspecific aggression, with beavers in large rivers having more injuries compared to ones in smaller streams (Crawford et al, 2015).…”
mentioning
confidence: 99%